EFEKTIVITAS PEMBERIAN DAUN KATUK DALAM MENINGKATKAN PRODUKSI ASI PADA IBU NIFAS DI PUSKESMAS CAMPAKA PURWAKARTA TAHUN 2021 - Widia Natalia (Fakultas Ilmu Kesehatan Unsika, 2021)
Breast milk is the best source of nutrients that can improve the health of mothers and children. Breastfeeding is very important, especially in the early period of life, therefore it is enough for babies to be exclusively breastfed for the first 6 months without adding and/or replacing with other foods or drinks. Breastfeeding immediately after delivery also helps uterine contractions thereby reducing maternal blood loss during the puerperium. The research used was a quasi-experimental (Quast Experiment) with a sample of 36 postpartum mothers. The sample size was 18 for each control and intervention group. Data analysis was carried out by univariate and bivariate using Shapiro-Wilk uni normality test the validity of the Mann-Whitney U test. Giving katuk leaves for 5 days in the intervention group and the control group. showed that of the 36 out of the total number of postpartum mothers who experienced a lot of breast milk production, 19 people with a presentation of 52.8% of the 36 mothers. From the results of statistical tests on giving katuk leaves, P value = 0.000 < 0.05, age P value was obtained 0.784> 0.05 and parity was obtained P value 0.597> 0.05, which means that both cannot affect breast milk production in postpartum mothers. . In dietary restrictions, the P value = 0.000 <0.05. So it can be concluded that there is a significant difference in the average giving of katuk leaves and dietary restrictions, which means that both can affect the increase in breast milk production in postpartum mothers Keywored : katuk leaves, milk production, postpartum.